Pressure dependence of the metal-insulator transition in κ-(BEDT-TTF)2Hg(SCN)2Cl: optical and transport studies. (12th December 2016) - Löhle, A; Rose, E; Singh, S; Beyer, R; Tafra, E; Ivek, T; Zhilyaeva, E I; Lyubovskaya, R N; Dressel, M
Abstract: The two-dimensional organic conductor κ -(BEDT-TTF)2 -Hg(SCN)2 Cl exhibits a pronounced metal-insulator transition at T C O = 30 K. From the splitting of the molecular vibrations, the phase transition can be unambiguously assigned to charge-ordering with 2 δ ρ = 0.2 e . We have investigated the pressure evolution of this behavior by temperature-dependent electrical transport measurements and optical investigations applying hydrostatic pressure up to 12 kbar. The data reveal a mean-field like down-shift of T C O (   p ) with a critical pressure of p c = 0.7 ± 0.1 kbar and a metallic state above the suppression of the charge-ordered state; no traces of superconductivity could be identified down to T   =  1.5 K. As the charge order δ ρ sets in abruptly with decreasing temperature, its size remains unaffected by pressure. However, the fraction of charge imbalanced molecules decreases until it is completely absent above 1.6 kbar.